Liver Transplantation Versus Liver Resection for Stage I and II Hepatocellular Carcinoma: Results of an Instrumental Variable Analysis - Li, Wei; Xiao, Haitao; Wu, Hong; Xu, Xuewen; Zhang, Yange (Frontiers in Oncology, 2021)
Background This study aimed to compare the long-term outcomes of liver transplantation (LT) and liver resection (LR) among patients with stage I and II hepatocellular carcinoma (HCC). Methods SEER 18 registry from 2004 to 2015 was retrieved for this study. We included 1,765 and 1,746 cases with stage I–II (AJCC, 7th) HCC in the multivariable analyses and instrumental variable (IV) analyses, respectively. Propensity score matching (PSM) was further carried out to ensure comparability. Propensity score to receive LT was adjusted by stabilized inverse probability of treatment weighting (IPTW) and standardized mortality ratio weighting (SMRW) methods. In addition, IV analysis was performed to adjust both measured and unmeasured confounding factors. Results We identified 1,000 (56.7%) and 765 (43.3%) patients treated with LR and LT, respectively. In the multivariable adjusted cohort, after adjusting potential confounders, patients undergoing LT offered significant prognostic advantages over LR in overall survival (OS, P < 0.001) and disease-free survival (DSS, P < 0.001). The instrument variable in this study is LT rates in various Health Service Areas (HSAs). Results from the IV analysis showed that cases treated with LT had significantly longer OS (P = 0.001) and DSS (P < 0.001). In IV analysis stratified by clinicopathologic variables, the treatment effect of LT vs. LR in OS was consistent across all subgroups. Regarding DSS in IV analyses, the subgroup analyses observed that LT had better DSS across all subgroups, except for similar results in the older patients (interaction P value = 0.039) and the non-White patients (interaction P value = 0.041). In the propensity-matched cohort, patients with LT still had better OS (P < 0.001) and DSS (P < 0.001) in comparison to cases who underwent LR. In both IPTW and SMRW cohorts, patients who underwent LT had better OS (both P values < 0.001) and DSS (both P values < 0.001). Conclusions LT provided a survival benefit for cases with stage I–II HCC. These results indicated that if LT rate was to increase in the future, average long-term survival may also increase. However, for some special populations such as the elderly patients, owing to the similar outcomes between LT and LR, the selection of LT should be cautious.